Acquired pendular nystagmus with oscillopsia in multiple sclerosis: a sign of cerebellar nuclei disease. Issue 5 (May 1974) - Aschoff, Jürgen C.; Conrad, B.; Kornhuber, H. H.
Abstract : In an unselected series of 644 cases of multiple sclerosis, 25 cases with acquired pendular nystagmus were found. Ten additional cases of pendular nystagmus in multiple sclerosis were investigated, and four cases from the literature are analysed. Acquired pendular nystagmus is purely sinusoidal in form, ceases with eye closure, is accompanied by oscillopsia, often monocular and vertical in direction, and never accompanied by optokinetic inversion. This is different from congenital nystagmus. Acquired pendular nystagmus in multiple sclerosis shows a high correlation with holding tremor of head and arm and with trunk ataxia, and must therefore be viewed as a result of lesions of cerebellar nuclei or their fibre connections with the brain-stem. Supporting evidence is discussed. The results fit into a theory of cerebellar function according to which the cerebellar nuclei are involved in the maintenance of positions.